What Determine Performance of Financial Accounting Lecturers? An Experimental Study in Indonesian Higher Education Institutions - Warsono-bin-Hardono, Sony; Pranesti, Arin; Rohma, Frida Fanani; Priambodo, Devandani Ken (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This study investigates the determinants of performance of financial accounting lecturers and instructors in Indonesia. The factors analyzed are competence, rigor, and thoroughness. The data was collected through experiment involving 110 instructors who are lecturers and instructors from universities, colleges, and polytechnic institutions in Indonesia. The participants were invited to the experiemental activity conducted in September 2016. The results show that competence, rigor, and thoroughness have positive effects on the performance of accounting instructors. The findings also confirm that competence, rigor, and thoroughness are the main qualities they must possess to perform optimally in their duties